Ways of improvement of company competitiveness (Вестник КазНУ. Серия Экономическая, 2016)
Improvement of competitiveness very important element for existence in market economy. It is difficult for companies to make an integrated approach for competitiveness increase. The company have to make an as sessment of competitiveness and make the analysis of the market. Mechanism of management of competitiveness guide in this case. Management of competitiveness gives a set of privileges which are capable to lift the company in leaders. The mechanism of management of competitiveness has to be part of each company which wants to be leaders in market economy.